RESIDING THE PLACE’S INCONVENIENCES WITH WORDS. A JESUIT EXERCISE OF POLITICAL ADAPTION AND TERRITORIAL DOMAIN IN THE SOUTHERN FRONTIER OF CHILE, 1700. - Gaune Corradi, Rafael (Revista de Historia Social y de las Mentalidades, 2012)
The reports presented by the Jesuit missionaries in Santiago’s “Junta de Misiones” in 1700, show that the Jesuit writing is involved in the construction of a space full of supernatural, strange and magic events. Through exaggerated writings, the Society of Jesus tried to achieve political, religious and economic advantages, by seducing and convincing with an illustration of a controlled, christianized and pacified space.
Keywords: Junta de Misiones; Jesuits; Reports of Missionaries; Writing; Space